The Holsteinian Interglacial river network of mid-eastern Poland and western Belarus - MARKS, LESZEK; PAVLOVSKAYA, IRINA E. (Boreas, 2003)
The Holsteinian drainage system in mid-eastern Poland and western Belarus has been reconstructed using palaeogeographical analysis based on abundant boreholes. The stratigraphic setting and palaeogeography are determined by correlation with Holsteinian marine sediments in the Kaliningrad District of Russia and the Late Elsterian glaciolacustrine series in the southern peribaltic region. At the beginning of the Holsteinian there were numerous residual overflow lakes at the Polish-Belarusian border area that gradually became interconnected with the Holsteinian Neman River and its tributaries. The base level of erosion is located in river beds of Holsteinian valleys slightly beneath beds of the recent rivers and indicates that Holsteinian sea level was apparently lower than the present Baltic Sea level. The Holsteinian Neman flowed southwestwards across the Biebrza River Basin to the Warsaw Basin. The main watershed between the Baltic Sea and the Black Sea was further to the west than its present location. The secondary watershed in northern Poland has only been slightly modified since that time.